Role of biomarkers in management of laryngeal dysplasia: a systematic review - Hussain, Tanvir; Matin, Abdul; Ali, Tamam Abou; Almanassra, Alaa (International Journal of Research in Medical Sciences, 2026)
Laryngeal dysplasia is a premalignant lesion with variable potential for progression to laryngeal squamous cell carcinoma, highlighting the need for reliable biomarkers that can improve diagnosis, risk stratification, and patient surveillance. This systematic review evaluated the current evidence regarding the role of molecular and histological biomarkers in the management of laryngeal dysplasia. A comprehensive literature search of PubMed, Scopus, Web of Science, and Google Scholar was conducted for studies published between January 2020 and September 2025 in accordance with the PRISMA 2020 guidelines. Twenty-four eligible studies were included after screening 2,847 records. Data regarding biomarker type, study design, testing methods, and diagnostic and prognostic outcomes were extracted and synthesized qualitatively. The evidence demonstrated that overexpression of p53, Ki-67, and PD-L1 was consistently associated with an increased risk of malignant transformation. Dysregulated microRNAs, particularly miR-21, miR-146, and miR-223, together with DNA methylation markers, also showed promising diagnostic and prognostic utility. Combined biomarker panels consistently outperformed conventional histopathology alone, achieving reported sensitivity of up to 89% and specificity of up to 84% for predicting malignant transformation. Although the current evidence supports the potential clinical value of these biomarkers as adjuncts to histopathological assessment, considerable heterogeneity in study design, laboratory techniques, and reporting limits their routine clinical application. Further well-designed multicenter prospective studies with standardized biomarker assessment protocols are required before these biomarkers can be incorporated into routine clinical practice for the diagnosis, prognostication, and follow-up of patients with laryngeal dysplasia.